2020
DOI: 10.1103/physrevresearch.2.033380
|View full text |Cite
|
Sign up to set email alerts
|

Pump-probe spectroscopy of Bose polarons: Dynamical formation and coherence

Abstract: We propose and investigate a pump-probe spectroscopy scheme to unveil the time-resolved dynamics of fermionic or bosonic impurities immersed in a harmonically trapped Bose-Einstein condensate. In this scheme a pump pulse initially transfers the impurities from a noninteracting to a resonantly interacting spin state and, after a finite time in which the system evolves freely, the probe pulse reverses this transition. This directly allows us to monitor the nonequilibrium dynamics of the impurities as the dynamic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 129 publications
(221 reference statements)
3
60
0
Order By: Relevance
“…Furthermore, it would be intriguing to study the persistence and possible alterations of the identified spatial configurations in the presence of finite temperature which will impact the coherence of the lattice bosons [88][89][90]. Another perspective is to investigate the relevant radiofrequency spectrum [31,43] in order to capture the emergent polaron properties including their lifetime, residue and effective mass especially in the attractive interaction regimes of bound state formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it would be intriguing to study the persistence and possible alterations of the identified spatial configurations in the presence of finite temperature which will impact the coherence of the lattice bosons [88][89][90]. Another perspective is to investigate the relevant radiofrequency spectrum [31,43] in order to capture the emergent polaron properties including their lifetime, residue and effective mass especially in the attractive interaction regimes of bound state formation.…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant ingredient is the external trapping geometry that the two components experience. Indeed, for harmonically trapped and homogeneous systems remarkable dynamical features of impurity physics include the spontaneous generation of localized patterns [17,[37][38][39], inelastic collisional aspects of driven impurities [40][41][42] with the surrounding and their relaxation at long timescales [43][44][45]. On the other hand, when a lattice potential is introduced the situation becomes more complicated giving rise, among others, to doped insulator physics [46,47] and impurity transport [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…The second method is called the multi-layer multi-configuration time-dependent Hartree method for atomic mixtures (ML-MCTDHX) [16] (see also a relevant review on the topic [52]). It is a variational approach that has been extensively used, among others, for studying systems with impurities [41,42,[53][54][55][56].…”
Section: Appendix a Numerical Methodsmentioning
confidence: 99%
“…These systems are inherently related to the so-called polaron concept [40,41], which is originally introduced in the context of a mobile impurity immersed in a quantum many-body environment with the former becoming dressed by the excitations of the bath [42][43][44][45]. So far, notable investigations of the emergent polaron properties in the ultracold atomic realm unveil, for example, their effective mass [35,[46][47][48][49], the underlying excitation spectra [50][51][52][53][54], the existence of bath mediated induced-interactions [55][56][57][58][59][60], as well as the orthogonality catastrophe (OC) mechanism [61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%